Merancang Aplikasi Inventory Support IT Berbasis WEB Pada PT Cahaya Lestari Permai Abadi - Rama Dwi Saputra; Raja Fadhilah Hamdan; Vini Delviani; Khalil gibran Almaulidi; Aries Saifudin (Jurnal Informatika Universitas Pamulang, 2022)
Designing a Web-Based IT Stock Inventory Support Application at PT Cahaya Lestari Permai Abadi made using HTML, PHP, MySQL, and DRAW.IO will support the efficiency and effectiveness of the company's work in storing and processing data so that it gets the information needed. The purpose of writing this Practical Work Report is to study, analyze, and design. A web-based information system at PT Cahaya Lestari Permai Abadi in particular to support the company's operational activities. The software developed in making this application uses HTML (Hypertext Markup Language) which is the basic language for web scripting and is a client-side which allows displaying information in the form of text, graphics, and also to connect between web page displays (hyperlinks). In addition, for data storage and processing, the programming language PHP (PHP Hypertext Preprocessor) and MySQL database are also used. The final result of this Practical Work Lecture is a web-based application design that can provide a clear picture of inputting IT inventory support at PT Cahaya Lestari Permai Abadi.